Corporate environmental compliance and sustainability in palm oil plantation activities - Putra, Bima Adi; Aipassa, Marlon I.; Ruslim, Yosep; Siahaya, Martha E. (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: One key aspect of sustainable palm oil industry development is responsible environmental management. The Indonesian government, through the Ministry of Agriculture, mandates that oil palm plantation companies implement Indonesia Sustainable Palm Oil (ISPO) standards. A crucial requirement includes conducting an Environmental Impact Analysis (EIA) and obtaining environmental permits. Companies must enhance their sustainability performance, particularly in environmental management. Methods: The research method used is to review environmental management documents and evaluate the results of laboratory analysis that have been obtained by PT. T. Data collection in this study was carried out through observation, interviews and literature studies. This study aims to examine the effectiveness of the implementation or implementation of the RKL-RPL of Oil Palm Plantations of PT. T with reference to environmental documents. Findings: Findings indicate that PT. T's Environmental Impact Analysis/Analisis Dampak Lingkungan (AMDAL) implementation complies with regulatory requirements. The Environmental Management Plan/Rencana Pengelolaan Lingkungan (RKL)—Environmental Monitoring Plan/Rencana Pemantauan Lingkungan (RPL) implementation is considered effective due to strong internal and external communication and coordination. Effective environmental management is driven by clear policies, standard operating procedures (SOPs), and competent human resources. Additionally, the company benefits from a well-structured organization, sufficient facilities, and adequate funding. Conclusion: The implementation of PT T's Environmental Management Plan/Rencana Pengelolaan Lingkungan (RKL)—Environmental Monitoring Plan/Rencana Pemantauan Lingkungan (RPL) in environmental management has been effective due to intensive communication, internal-external coordination, and the support of clear policies and standard operating procedures (SOPs). This success is supported by competent human resources, a well-structured organization, as well as adequate facilities and funding. Novelty/Originality of this article: The novelty of this research lies in its comprehensive evaluation of corporate environmental management effectiveness, offering valuable insights into best practices for sustainable palm oil production in Indonesia.